Rebirthing a nation : white women, identity politics, and the internet - Anderson, Wendy K. Z. (Race, rhetoric, and media series., 2021)
"Although US history is marred by institutionalized racism and sexism, postracial and postfeminist attitudes drive our polarized politics. Violence against people of color, transgendered and gay people, and women soar upon the backdrop of Donald Trump, Tea Party affiliates, alt-right members like Richard Spencer, and right-wing political commentators like Milo Yiannopoulos who defend their racist and sexist commentary through legalistic claims of freedom of speech. While more institutions recognize the volatility of these white men's speech, few notice or have thoughtfully considered the role of white nationalist, alt-right, and conservative white women's messages that organizationally preserve white supremacy. In Rebirthing a Nation: White Women, Identity Politics, and the Internet, author Wendy K. Z. Anderson details how white nationalist and alt-right women refine racist rhetoric and web design as a means of protection and simultaneous instantiation of white supremacy, which conservative political actors including Sarah Palin, Donald Trump, Kellyanne Conway, Sarah Huckabee Sanders, and Ivanka Trump have amplified through transnational politics. By validating racial fears and political divisiveness through coded white identity politics, postfeminist and motherhood discourse functions as a colorblind, gilded cage. Rebirthing a Nation reveals how white nationalist women utilize colorblind racism within digital space, exposing how a postfeminist framework becomes fodder for conservative white women's political speech to preserve institutional white supremacy"--